Verification of structural elements made of FRC only: A critical discussion and proposal of a novel analytical method. (15th January 2017) - Facconi, Luca; Minelli, Fausto
Highlights: Deficiencies of the provisions for FRC structures containing fibers only in MC2010. New design approach based on the bi-linearization of the global structural response. Proposal of a new set of equations for checking FRC structures both al ULS and SLS. Validation of the new approach against numerical and experimental available data. The novel approach is more conservative than that included in MC2010. Abstract: The recent fib Model Code for Concrete Structures 2010 (MC2010) recognizes fiber reinforced concrete (FRC) as a new structural material, favoring its usage in innovative structural applications. FRC is considered primarily a material with a non-negligible residual strength after cracking. According to MC2010, FRC can be adopted as the only reinforcement in structures provided that both strength and ductility requirements are fulfilled. This paper presents a discussion on the MC2010 requirements for FRC structures applied to both experimental and numerically simulated structural elements, proposing a refined set of equations to check FRC structures (not containing any classical reinforcement) against both service and ultimate limit states.